Toward a parallel and cascading model of the writing system: A review of research on writing processes coordination - Olive, Thierry (Journal of Writing Research, 2014)
Efficient coordination of the different writing processes is central to producing good-quality texts, and is a fundamental component of writing skill. In this article, I propose a general theoretical framework for considering how writing processes are coordinated, in which writing processes are concurrently activated with more or less overlap between processes depending on their working memory demands, and with the flow of information cascading from central to peripheral levels of processing. To support this view, I review studies that investigated effects of handwriting skills on concurrent activation of higher order processes, and research on word production that explored how information cascades between levels of processing in the writing system. I argue that a parallel and cascading model makes it possible to combine different findings in a common integrated framework and thus constitutes a heuristic for further understanding coordination of the different levels of processing involved in writing.